Peluang Usaha Industri Pariwisata di Jakarta Selatan - Dyah Budiastuti; Andri Andri; Agus Agus (Binus Business Review, 2010)
Well-managed tourism will be capable of contributing to the increase in local revenues and be capable to attract investors and open up jobs. Lack of socialization of the tourism potential in a region becomes an obstacle for investors to get involved in it. This research aims to identify the business opportunities of tourism industry and potential of tourism industry in South Jakarta. Data are obtained from the Suku Dinas Pariwisata Jakarta Selatan and analyzed with descriptive statistical methods. The results show that Setiabudi District has an opportunity for hospitality business; Mampang Prapatan, Pasar Minggu, and Kebayoran Baru District have opportunities for recreation and entertainment business.